Population-level changes to promote cardiovascular health. - Jørgensen, T; Capewell, S; Prescott, E; Allender, S; Sans, S; Zdrojewski, T; De Bacquer, D; de Sutter, J; Franco, O; Løgstrup, S; Volpe, M; Malyutina, S; et al. (2013)
BACKGROUND: Cardiovascular diseases (CVD) cause 1.8 million premature (<75 years) death annually in Europe. The majority of these deaths are preventable with the most efficient and cost-effective approach being on the population level. The aim of this position paper is to assist authorities in selecting the most adequate management strategies to prevent CVD. DESIGN AND METHODS: Experts reviewed and summarized the published evidence on the major modifiable CVD risk factors: food, physical inactivity, smoking, and alcohol. Population-based preventive strategies focus on fiscal measures (e.g. taxation), national and regional policies (e.g. smoke-free legislation), and environmental changes (e.g. availability of alcohol). RESULTS: Food is a complex area, but several strategies can be effective in increasing fruit and vegetables and lowering intake of salt, saturated fat, trans-fats, and free sugars. Tobacco and alcohol can be regulated mainly by fiscal measures and national policies, but local availability also plays a role. Changes in national policies and the built environment will integrate physical activity into daily life. CONCLUSION: Societal changes and commercial influences have led to the present unhealthy environment, in which default option in life style increases CVD risk. A challenge for both central and local authorities is, therefore, to ensure healthier defaults. This position paper summarizes the evidence and recommends a number of structural strategies at international, national, and regional levels that in combination can substantially reduce CVD.